The development and progress of nanomedicine for esophageal cancer diagnosis and treatment. (November 2022) - Li, Xiaokun; Chen, Lingmin; Luan, Siyuan; Zhou, Jianfeng; Xiao, Xin; Yang, Yushang; Mao, Chengyi; Fang, Pinhao; Chen, Longqi; Zeng, Xiaoxi; Gao, Huile; Yuan, Yong
Abstract: Esophageal cancer (EC) is a common gastrointestinal malignancy with poor prognosis and high mortality. Although combined therapeutic strategies have been developed, the 5-year survival rate of patients with EC remains relatively poor. Conventional anti-cancer drug delivery techniques have some shortcomings, such as nontargeted delivery and nonspecific toxicity. Nanoparticles (NPs) provide a promising platform for delivering drugs in various therapeutic modalities for EC, which possess several remarkable advantages in cancer therapy, such as reduced side effects, prolonged circulation time, and preferential accumulation at the tumor site. In this review, we summarized various types of NPs applied in the treatment of EC, including polymers, micelles, liposomes, inorganic NPs and organic NPs. Meanwhile, we discussed the efficacy and safety of newly designed nanomedicine in various treatments of EC, including chemotherapy, radiotherapy, gene therapy, photodynamic therapy (PDT), photothermal therapy (PTT), and their synergetic therapy. In addition, nanomedicine applied in tumor imaging and diagnoses were also reviewed. Current studies have suggested the potential advantages of nanoformulations over conventional formulations. More researches to promote clinical translation of nanomedicine for EC are anticipated in the future.